Thermal induced changes of rice straw phytolith in relation to arsenic release: A perspective of rice straw arsenic under open burning. (15th February 2022) - Nguyen, Minh N.; Nguyen, Anh T.Q.; Dultz, Stefan; Tsubota, Toshiki; Duong, Lim T.; Nguyen, Anh M.; Pham, Nga T.T.
Abstract: On-site open burning is a common practice for handling rice straw, but its negative impacts, e.g., biomass loss and air pollution, are largely debated worldwide. To address the negative effects of open burning, many efforts have been made to 'ignite' worldwide bans. However, these bans are likely based on a singular view in which some positive aspects of open burning are overlooked. In this study, we aimed to determine the thermal-induced changes of straw and straw arsenic (As) under open burning and heat-treatments (in the temperature range from 300 to 900 °C). It was found that silica phase in rice straw (so-called phytolith) can encapsulate As in its structure. Open burning or heat-treatment of straw resulted in a tighter association of As and phytolith, thereby reducing dissolution of As. We proposed an opinion that open burning causes air pollution, but it can increase the activity of phytolith in sequestrating As, enabling delayed As cycle in rice ecosystems. The combat of on-site open burning of rice straw to reduce air pollution will alter straw handling routines, thereby changing the cycle of straw phytolith and the route of straw As. Graphical abstract: Image 1 Highlights: Precipitation of Si in rice plant can form a silica skeleton, so-called phytolith. The evolution of phytolith can encapsulate As into its structure. Thermal treatment involves As in straw in a tighter association with phytolith. This association makes As more recalcitrant and leads to a delayed release of As.